Modified APC-OMS Technique for Memory Based Computing. (2016) - Paul, Liya; Paul, Reen
Abstract: In digital signal processing (DSP) memory based computing plays a vital role for to meet the progressive requirements of DSP. The memory based computing includes antisymmetric product coding (APC), odd multiple storage (OMS), APC-OMS technique. This paper compares the memory based computing techniques APC technique, OMS technique with the modified APC-OMS based lookup-table (LUT) multiplier in terms of area and speed and they are coded in Verilog HDL and synthesized in Xilinx ISE Design suite 14.2 and Cadence 90 nm Technology The proposed APC-OMS based look-up table (LUT) multiplier can optimize the LUT size and it consumes less area and obtains high speed as compared to other techniques.